Principles of environmental science and technology - Saravanan, K.; Ramachandran, S.; Baskar, R. (New Age International (P) Ltd., Publishers, 2005)
This book is meant to be an introductory text on the Fundamentals of Environmental Science and Engineering. Today, knowledge of Environmental Science is essential for students as well as practicing engineers and scientists of all disciplines. Here an attempt has been made to provide precise and upto date information on the fundamental aspects of Environmental Science and Engineering without going much in-depth in to specific areas, so as to be useful for a cross section of fields of study. Indian technical universities are making the study of Environmental Science and Engineering mandatory for
Keywords: Environmental sciences : Study and teaching (Higher); Environmental protection : Study and teaching (Higher); Environmental engineering : Study and teaching (Higher); Pollution